Prevalencia del síndrome metabólico y relación con valores antropométricos, exámenes bioquímicos, factores alimentarios, actividad física y consumo de alcohol y tabaco en el personal administrativo de la universidad internacional del ecuador, sede principal, en el periodo 2011 – 2012. - Malo Villagomez, Carla Maria (2014)
Objective: Identify prevalence of metabolic syndrome in people who worked at Universidad Internacional del Ecuador in 2011, using the criteria of ATP III and IDF, from the anthropometric, biochemical tests, dietary factors, physical activity and alcohol consumption and and cigarettes consumption. Method: A descriptive cross-sectional study which prevalence rates of nutritional status by dietary factors and biochemical tests were performed was determined. Personal and family history was identified and they also assessed the association of the same. The sample 132 individuals, of whom 72 were men and 60 women, between 20 and 74 years old, administrative workers, maintenance, equestrian and security of Universidad International del Ecuador. Results: According to research, the results show that the prevalence of metabolic syndrome according to the ATP III criteria is 32.6% (43/132), which 38.9% (28/43) were men, 55.9% (24 / 43) were married, 34.9% (15/43) are between 20-30 years old, 62.8% (27/43) received higher education, and 65.1% (28/43) are administrative workers. The same happens with the results found according to the IDF criteria 43.18% (57/132). Of these, 45.8% (33/57) were men, 54.4% (31/57) were married, 33.3% (19/57) are between 20-30 years old, 68.4% (39/57) have higher education, and 70.2% (40/57) are workers in the administrative area...